The metabolomic plasma profile of myeloma patients is considerably different from healthy subjects and reveals potential new therapeutic targets - Steiner, Normann; Müller, Udo; Hajek, Roman; Sevcikova, Sabina; Borjan, Bojana; Jöhrer, Karin; Göbel, Georg; Pircher, Andreas; Gunsilius, Eberhard (PLoS One, 2018)
INTRODUCTION: Multiple myeloma (MM), a malignant plasma cell disorder, is still an incurable disease. Thus, the identification of novel therapeutic targets is of utmost importance. Here, we evaluated the peripheral blood-based metabolic profile of patients with MM. MATERIAL & METHODS: Peripheral blood plasma levels of 188 endogenous metabolites, including amino acids, biogenic amines, acylcarnitines, glycerophospholipids, sphingomyelins, and hexoses were determined in patients with plasma cell dyscrasias: monoclonal gammopathy of undetermined significance, a precursor stage of MM (MGUS, n = 15), newly diagnosed MM, (NDMM, n = 32), relapsed/refractory MM (RRMM, n = 19) and in 25 healthy controls by mass spectrometry. RESULTS: Patients with NDMM, RRMM and MGUS have a substantially different metabolomic profile than healthy controls. The amount of eight plasma metabolites significantly differs between the NDMM and MGUS group: free carnitine, acetylcarnitine, glutamate, asymmetric dimethylarginine (ADMA) and four phosphatidylcholine (PC) species. In addition, the levels of octadecanoylcarnitine, ADMA and six PCs were significantly different between RRMM and MGUS patients. 13 different concentrations of metabolites were found between RRMM and NDMM patients (free carnitine, acetylcarnitine, creatinine, five LysoPCs and PCs). Pathway analyses revealed a distinct metabolic profile with significant alterations in amino acid, lipid, and energy metabolism in healthy volunteers compared to MGUS/MM patients. CONCLUSION: We identified different metabolic profiles in MGUS und MM patients in comparison to healthy controls. Thus, different metabolic processes, potentially the immunoregulation by indoleamine 2,3 dioxygenase-1 (IDO), which is involved in cancer development and progression supporting inflammatory processes in the tumor microenvironment and glutaminolysis, can serve as novel promising therapeutic targets in MM.
Keywords: monoklonální gamapatie nejasného významu; Aged; Biomarkers; Female; biologické markery; senioři nad 80 let; Aged, 80 and over; Case-Control Studies; senioři; Humans; Monoclonal Gammopathy of Undetermined Significance; metabolom; Metabolomics; metabolomika; metabolické sítě a dráhy; lidé středního věku; lidé; mužské pohlaví; studie případů a kontrol; mnohočetný myelom; Male; ženské pohlaví; Metabolic Networks and Pathways; Middle Aged; Multiple Myeloma; Metabolome